THE HUMAN RIGHTS PROTECTION IN THE ECONOMIC AFFAIRS OF INDONESIA - Siti Rodhiyah Dwi Istinah; Sri Kusriyah; Rakhmat Bowo Suharto (Jurnal Pembaharuan Hukum, 2021)
The purpose of this study is to analyze and explain the protection of human rights in the economic sector for citizens to be able to enjoy a socially just economic development as well as to analyze and explain the challenges and obstacles in protecting human rights in the economic sector in an effort to realize social justice in the Constitution 1945. important in the constitution which gave birth to the concept of protecting human rights in the economic sector, which was initiated by the founding fathers, regarding Indonesian socialism. Hatta's idea was in line with Soekarno's thinking as "Indonesian-style socialism" which was adapted to Indonesian conditions. Qualitative research with normative juridical research type with secondary data by means of literature study. The conclusions of this study are 1) so far regulations have not provided much protection for human rights in the economic field, because they are against the principles of economic democracy in Article 33 of the Constitution 1945, so that the interests of citizens are marginalized. 2) regulations so far have more accommodated the principles adhered to by developed countries, the emergence of the era of liberalization, world trade without protection and without obstacles, will increase the level of trade competition among economic actors in Indonesia.